Diskusi filioque - Hutagalung, Pitta Uli; Timo, Eben Nuban (Te Deum (Jurnal Teologi dan Pengembangan Pelayanan), 2023)
The filioque controversy between East and West had quite a crucial impact, such as the schism in 1054. Not only territorial, the impact was also on the theological development of each party. According to the needs of the context, the East has a pneumatological pattern, while the West has a Christological style. different developments influenced theology in different places. One of them is the theology in Indonesia which is unique because it has a wealth of Eastern traditions, but has a Western theology style. This uniqueness needs to be managed properly by the church in theology according to the context. Be concerned if the church is antipathy towards the tradition of its context, for example the church's rejection of local wisdom. Because of that, this paper wants to describe a meaning of the filioque controversy which is expected to inspire the church in Indonesia in developing its theology.